First fetal case of the 8q24.3 contiguous genes syndrome. Issue 1 (5th October 2015) - Wells, Constance; Spaggiari, Emmanuel; Malan, Valérie; Stirnemann, Julien J.; Attie‐Bitach, Tania; Ville, Yves; Vekemans, Michel; Bessieres, Bettina; Romana, Serge
Abstract : Molecular cytogenetics, particularly array‐CGH, opened the way to the « genotype first approach » and for the discovery of new micro rearrangement syndromes. This was the case for the 8q24.3 microdeletion syndrome. Here, we describe the phenotype of a fetus with a 8q24.3 deletion. This rare condition has to be considered as a contiguous genes syndrome because its phenotype is generated by the SCRIB and PUF60 adjacent gene endophenotypes. The fetus presented atrioventricular septal defect and hypoplastic aortic arch, facial dysmorphism, microretrognathia, dysmorphic ears, clinodactyly of the 5th digit on both hands, mild rocker bottom feet and abnormal third sacral vertebra. This fetus is the first case where the endophenotype produced by SCRIB gene is absent. This case is compared with the previous published cases. © 2015 Wiley Periodicals, Inc.